Preference for sons: still a trend? Evidence from individual-level data from Finland, 1960–2015 - Krista Riukula (Review of Economics of the Household, 2024)
Abstract Preference for sons has been shown in various ways, but is it still up to date? I investigate how sex preference has evolved during the past 50 years using population-wide data from Finland. I find that having a first-born girl increases fertility and decreases the probability of being together with the child's father in the 1960s to 1980s but not after the 1990s. Families with a first-born girl had 0.03 more children in the years 1960–1980. The effect decreases to an imprecise zero in the 1990s and to 0.007 fewer children in the 2000s. This shift occurs at the same time as the female and male employment rates approach each other. As the costs of raising a girl are not greater than those of raising a boy in Finland, the results suggest that the shift might be due to increased female bargaining power. Past literature has shown that females prefer girls over boys or are more neutral than males, who prefer having sons over daughters more often.
Additional information: J1;J11;J12;J13;J16
Keywords: 330; Child sex; Son preference; Fertility; Family structure; Marriage